From graphene oxide to reduced graphene oxide: Enhanced hydration and compressive strength of cement composites. (10th July 2020) - Jing, Guojian; Wu, Jiaming; Lei, Tianyu; Wang, Shuxian; Strokova, Valeria; Nelyubova, Viktoria; Wang, Mingjun; Ye, Zhengmao
Highlights: GO could enhance cement hydration degree and promote the formation of crystals. Cement with original GO manifest higher hydration degree and compressive strength. The oxygen-containing groups play a critical role in GO-cement composites. Abstract: Despite amazing recent progress on graphene oxide (GO) modified cement composites, the effects of oxygen-containing functional groups of GO on cement properties have not been explored. This study presents the measurements of hydration process, microstructure and compressive strength of cement composites coated by original and reduced GO. Reduced GO is obtained by carrying out the annealing treatment at 300 °C for 60 min. Results show the incorporation of pristine and reduced GO could accelerate cement hydration and promote the formation of crystals due to the nucleation sites effect. The hardened cement paste with original 0.6 wt% GO increases approximately 23.66% hydration degree, while the corresponding increase percentage of cement after annealing is 4.92%. The increments in compressive strength are 8.19 & 15.07% at 3 days and 0.85 & 1.30% at 28 days, which are much higher than that with reduced GO (the increased rates are 2.91 & 7.42% at 3 days and 0.08 & 0.54% at 28 days). The amounts of oxygen-containing groups play a critical role in formulating GO-cement composites. The outcomes of this research develop a new avenue to deeply understand the role of oxygen groups of GO in cement composites.